Effect of variable helix and pitch tool geometries on process damping performance in endmilling process - Muhammad Adib, Shaharun (2015)
The machining instability onset of chatter occurs when a complex interaction between machining structural systems and the cutting process especially in machining difficult-to-cut materials (titanium and nickel based alloy). This is because, the dynamic deflection of tool and workpiece systems generates unstable cutting forces when machining with a high material removal rate. Here, sudden large vibration amplitudes occur when energy input exceeds the energy dissipated from the system, leading to self-excited vibration or chatter. Previous study proposed that the so called ‘process damping’ phenomenon is particularly important for variable helix milling tools. Consequently, the contribution of this thesis is a study of variable helix and pitch tool on the process damping performance. Testing was performed for tools with different helix and pitch angle and process parameters onto the performance of process damping under the flexible condition. In addition to that, the effect of modal analysis and cutting force stiffness was also studied. By using flexural condition at 390 Hz of frequency neutral, all tool were tested in machining titanium alloy in order to stimulate the process damping phenomena by examining the chatter behaviour from acceleration signal in time domain data collection. The result obtained shows that uniform tool with 42o is the best helix angle compared to 37o, 45o and 52o with process damping wavelength, λc= 0.24 mm .While, the effect of tool geometries shows that variable helix (48o, 53o, 51o, and 47o) and variable pitch tools (60o, 63o, 107o, and 88o) has the highest process damping wavelength at 0.66 mm compared to uniform, variable helix uniform pitch and uniform helix variable pitch tools. In this study, the performance of process damping was in accordance with the attainment of cutting force results. In order to improvise process damping of variable helix and pitch tool, a study the influence of process machining parameters in terms of material removal rate and surface roughness was also conducted. The results obtained show that the machining parameter with 2.4 mm radial depth of cut was able to increase material removal rate at 8,103 mm3/min meanwhile the increment of spindle speed has shown to reduce the surface roughness and increased process damping wavelength to 0.68 mm. In this study, the effect of spindle speed increment percentage was also investigated. The results obtained shows that the occurrence of process damping was initiated at 2.5% as compared to 5 % and 7.5%. In conclusion, this study shows that the employment of variable helix and variable pitch tools in process damping has given the highest impact to suppress the chatter. Therefore, the variable helix and variable pitch endmill should represent as a promising tool to decrease the chatter effect in milling process especially for difficult-to-cut materials.